Impact of Diesel Vehicle Emissions on PM2.5 Concentrations in Seoul Metropolitan Area during the Seasonal PM2.5 Management - Kim, Yoonha; Kim, Eunhye; Kang, Yoon Hee; You, Seunghee; Bae, Minah; Son, Kyuwon; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
The impact of diesel vehicle emissions which accounts for a 90% of the on-road mobile NOX emissions in the Seoul Metropolitan Area (SMA) on PM2.5 concentration was estimated by the brute force method with the Community Multiscale Air Quality (CMAQ) model during the seasonal PM2.5 management from December 2019 to March 2020. The period mean impact of the SMA diesel vehicle emissions on the PM2.5 concentration was 0.8 μg/m3 over the SMA during the simulation period, which was led by organic carbon (OC, 0.4 μg/m3) and primary PM2.5 (0.4 μg/m3) rather than nitrate (0.0 μg/m3) formed from NOX. When the impact of NOX emissions from the diesel vehicle to the monthly mean nitrate was evaluated, the negative impact, so-called ‘NOX-disbenefit’, in which NOX reductions increased nitrate formation appeared in December 2019 (-0.5 μg/m3) and January 2020 (-0.1 μg/m3). An alternative air quality simulation with an additional 50% reduction of NOX emissions from all the emission sources except the on-road mobile greatly reduced the NOX-disbenefit effect. As a result, the NOX-reduced condition increased the overall impact of the SMA diesel vehicle emissions on PM2.5 and nitrate over the region by up to 1.3 μg/m3 and 0.5 μg/m3, respectively. It implies that even the same emission control may exhibit different effectiveness in the PM2.5 change depending on the NOX conditions. Thus, it is necessary to better understand how the non-linearity of the secondary PM2.5 formation plays a role in determining the overall impact of emission abatement plans to improve air quality over a region.
Keywords: Control effectiveness; Diesel vehicle emissions; NOX-disbenefit; NOX-to-nitrate conversion; Seasona l PM2.5 management